Prevalence of Malaria in General Populationof Distric Buner - Muhammad, Noor; Hussain, Akbar (Journal of Postgraduate Medical Institute, 2011)
To assess the prevalence of malaria in general population of Distt: Buner. From March to August 2001. total of 1020 blood films from 40 different localities of Distt: Buner was randoomly collected from both male and female of different age group (1 to 70) and were analysed in 40 different localities of district Buner. out of these, 70 individuals (6.86%) were positive for plasmodium. Teh plasmodium species found were P. vivax (5.78%) and P. falciparum (1.08%) with not a single case of mixed infections. Incidence was higher among the male (7.10%) as compared to female (6.52%). The higher rate of infections (11.58%) wasa found in age group 1 - 10 years and the lowest (5.19%) in age group 51 - 70 years. the highest rate of infections was recorded in August (11.66%) while the lowest rate of infection (3.98%) was noted in March. Slightly variation in prevalence of malaria was also observed in the four sectors A, B, C and D. the highest prevalence of infection (6.93%) was found in sector "C" where as the lowest infection (6.78%) was noted in sector "B". malaria is a common health problem in distt: Buner both P. vivax and P. falciparum exist. The higher rate of infection was found under the age of ten years (11.58%) and the maximum cases were noted in August (11.66%) while the lowest infection was noted in March the highest infection (6.93%) was founded in sector C where as the lowest infection (6.78%) was noted in sector "B".